PERAWATAN LUKA ULKUS DIABETIKUM: TINJAUAN LITERATUR - Setio Budi Raharjo; Ritawati Suratmin; Dinda Maulidia; Octa Pratiwi; Ridha Meutia Fidela (Journal Keperawatan, 2022)
Diabetes Mellitus (DM) is a chronic disease that is often found with diabetic foot wounds. Diabetic foot ulcers can occur partially (Partial Thickness) or completely (Full Thickness) in the skin area that extends to the subcutaneous tissue, tendons, muscles, bones or joints. DM patients with diabetic foot wounds require long-term care to recover. The purpose of this study was to explore several wound care techniques both modern and conventional. This study uses electronic databases from PubMed, Google Scholar, and Garuda. The inclusion criteria of the articles in this study are: publications in 2015 – 2020, full text, articles using English or Indonesian, and research methods using experimental studies with full text PDF format. Found 4 studies with details of 1 case study methods, 1 quasi-experimental method, and 2 observation method. All articles were analyzed using the PICO (Population, Intervention, Comparator, Outcome) method. After treating diabetic foot wounds through TIME management, it has been found that modern therapeutic methods show a significantly higher rate of diabetic foot wound healing compared to conventional therapeutic methods for various types of diabetic foot wounds. Thus, DM patients with diabetic foot wounds can recover through wound care using dry and moist principles where modern wound care techniques are more effective than conventional treatment techniques (using sterile gauze).